(3eedcI GdCfGJjNs - (3gRGY, efGQs; (3MSGe, HSeIs; (3NdjaI, NjGWs ((3GdbGgQIs (3YGdjI ddfTQ hGdJhRjYs, 2022)
(3CgdG hSgdG Hce aj eWHN eedcI GdCfGJjN, gfG jLJeY GdWHN eY GdLZQGajG hGdJGQjN hJJe OQGSI GdhUaGJ HhGSWI aQjb CfGJjNj Ydi CYdi GdeSJhjGJs
(3bUU YQHjIs
Keywords: (3GdbUU GdYQHjI GdbUjQIs -- (3eUQs; (3bUU GdCWaGds